Early Childhood Nutrition Is Positively Associated with Adolescent Educational Outcomes: Evidence from the Andhra Pradesh Child and Parents Study (APCAPS). Issue 4 (9th March 2016) - Nandi, Arindam; Ashok, Ashvin; Kinra, Sanjay; Behrman, Jere R; Laxminarayan, Ramanan
Abstract: Background: India's Integrated Child Development Scheme, which provides supplementary nutrition and other public health services to >91 million women and children aged <6 y, is the largest program of its kind in the world. Objective: We estimated the long-term associations of maternal and early childhood nutrition provided under the Integrated Child Development Scheme with educational outcomes when the children became adolescents. Methods: We used longitudinal data from a controlled nutrition trial conducted near the city of Hyderabad, India. From 1987 to 1990, a balanced protein-energy supplement (corn-soya meal, called upma ) was offered to pregnant women and children aged <6 y in 15 intervention villages, whereas no supplementation was offered in 14 control villages. Both groups had equal access to other public programs such as immunization and anemia control in pregnancy. Children born during the original trial period were resurveyed (654 intervention and 511 control group children) in 2003–2005. We used propensity score matching methods to correct for estimation bias in our regression models to assess the associations of supplementary nutrition with school enrollment, schooling grades completed, and academic test performance of these adolescents. Results: Children born in intervention villages were 7.8% (95% CI: 0.1%, 15.4%; P < 0.05) more likely to be enrolled in school and completed 0.84 (95% CI: 0.28, 1.39; P < 0.005) more schooling grades than children born in control villages. We found no association between supplementary nutrition and academic performance, as measured by school test scores. Conclusion: Offering a nutritional supplement to pregnant women and children <6 y of age during the Hyderabad Nutrition Trial was associated with improved school enrollment and completion of more schooling grades when the children became adolescents.